Investigating resistance of glioblastoma multiforme to radiotherapy and chemotherapy - Simpson, A (2016)
Glioblastoma multiforme (GBM) is the most common and aggressive type of brain tumour. Despite treatment with surgery, radiotherapy and temozolomide (TMZ) chemotherapy, patient survival remains poor, suggesting that GBM cells evade and resist these therapies. The insulin-like growth factor 1 receptor (IGF-1R) is a receptor tyrosine kinase that signals towards cellular survival, proliferation and motility. Previous work from our laboratory showed that IGF-1R inhibition sensitises other tumour types to ionising radiation (IR) and TMZ. The first aim of this project was to assess IGF-1R expression in brain tumour tissue microarrays by immunohistochemistry. IGF-1R was found to be upregulated in adult and paediatric tumours relative to normal brain. In paediatric brain tumour patients, higher IGF-1R expression was found to associate with reduced patient survival, but no association was observed for adult brain tumour patients. The second aim sought to assess the effect of IGF-1R inhibition on the sensitivities of GBM cell lines to IR and TMZ. Adult and paediatric GBM cells showed varied expression and activation of IGF-1R and downstream signalling components. Use of two IGF-1R axis inhibitors showed that paediatric, but not adult GBM cells were sensitive to IGF-1R inhibition. In addition, there was evidence that IGF-1R inhibition sensitised paediatric GBM cells to IR. These results suggest that the IGF-1R could be an important target in paediatric GBM. However, sensitisation to TMZ was not observed. The third aim of this project was to assess the effects of repeated TMZ or IR treatment on adult GBM cells in order to identify mediators of treatment resistance. Repeated treatment with TMZ allowed previously sensitive cells that lacked O6-alkylguanine-DNA alkyltransferase (MGMT) to acquire different degrees of resistance to TMZ. Characterisation of the induced resistance sublines showed detectable MGMT expression. However, unlike the TMZ resistance detected in two cell lines that expressed endogenous MGMT, the induced TMZ resistance in the repeatedly treated cells did not depend on MGMT activity. These MGMT-independent resistant cells may be useful to investigate novel strategies to overcome TMZ resistance. Finally, two repeatedly irradiated GBM sublines were established and characterised. One subline developed relative resistance to IR, the other developed a more motile phenotype. Microarray analysis showed differential expression of 122 genes across both cell line pairs, including upregulation of the stem cell marker CD24 in the more motile repeatedly irradiated subline. CD24 upregulation was validated at the mRNA and protein levels. Further investigation of differentially expressed genes may provide insights into novel mechanisms by which GBM cells evade or resist radiotherapy, and may help to guide development of new targeted treatments for GBM patients.